Reaction of Proton Pump Inhibitors With Model Peptides Results in Novel Products - Charles Watson; Lixin Zhu; Shenheng Guan; Terry E. Machen; John G. Forte (Elsevier, 2013)
The proposed mechanism for proton pump inhibitors (PPIs) is that PPIs are activated at low pH to the sulfenamide form, which reacts with the sulfhydryl group of cysteine(s) at the active site of the proton pump, to produce reducible disulfide-bonded PPI-proton pump conjugates. However, this mechanism cannot explain the observations that some PPI-protein conjugates are irreducible. This study was designed to investigate the chemistry of the irreducible conjugates by mass spectrometry, using three PPIs and 17 cysteine-containing peptides. While some peptides favored the formation of reducible PPI-peptide adduct, the other peptides mainly produced irreducible adducts. Characterization of the irreducible adduct revealed that the irreducible bonding required the participation of both a sulfhydryl group and a nearby primary amino group. High resolution mass spectrometry suggested a molecular structure of the irreducible adduct. These results suggested a reaction mechanism in which the PPI pyridone form reacted with an amino group and a sulfhydryl group to form an irreducible adduct. The irreducible adduct becomes the dominant product over time because of the irreversible nature of the pyridone-mediated reaction. These findings may explain the irreducible inhibition of H/K-ATPase by PPIs and their relatively slow biological turnover in vivo. [Supplementary materials: available only at http://dx.doi.org/10.1254/jphs.13058FP] Keywords:: proton pump inhibitor (PPI), omeprazole, lansoprazole, pantoprazole, mass spectrometry